2007
DOI: 10.1071/sh06050
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia trachomatis in a public colposcopy clinic population

Abstract: Although the prevalence of chlamydial infection in the colposcopy clinic population as a whole does not warrant a policy for routine screening, screening directed at women aged 25 years or less would gain the greatest yields in terms of cost efficacy. Such a policy should be implemented as standard practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Overall, history or current infection with an STI including Chlamydia was 27.6% in our study, which is worryingly high. Other studies have shown that the prevalence rate of Chlamydia in the colposcopy setting was between 5.8% and 8.9% 11,20 . This correlates with our results showing 9.2% had a history or current Chlamydia infection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, history or current infection with an STI including Chlamydia was 27.6% in our study, which is worryingly high. Other studies have shown that the prevalence rate of Chlamydia in the colposcopy setting was between 5.8% and 8.9% 11,20 . This correlates with our results showing 9.2% had a history or current Chlamydia infection.…”
Section: Discussionsupporting
confidence: 91%
“…This results in a largely preventable risk of acquiring STIs. Women seen in colposcopy clinic have already been identified as women potentially exposed to the HPV virus and therefore possible other undiagnosed STI’s 9,11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-primary care clinical settings, the chlamydia prevalence for women attending a colposcopy clinic was reported to be higher in women aged 25 years or less (5.8%) compared with older women (0.9%) [55]. A prevalence of just 0.2% was found for women attending a hospital in vitro fertilisation (IVF) service for investigation of infertility [54]; however, higher estimates for hospital-based studies of 3.1% for women [45] and 5.5% for men and women [56] were also reported.…”
Section: Resultsmentioning
confidence: 99%
“…1 Complications following chlamydia, gonorrhoea and trichomonas infections in women include pelvic inflammatory disease, chronic pelvic pain, tubo-ovarian abscesses, ectopic pregnancies and infertility. 2,3 In pregnancy these infections are associated with prematurity, neonatal morbidity and perinatal infections. 4,5 In men, these STIs may be complicated by epididymitis and result in urethral stricture and infertility (http://www.cdc.gov/std).…”
Section: Introductionmentioning
confidence: 99%